Production + Program: An Integrated Approach for the Revamping and Expansion of an Iron and Steel Making Facility: A Case Study - M., Waris; Asim, Zeeshan (ESB Business School, 2016)
Iron and steel consumption is a vital indicator for the development of any industrialized country. The major steel consuming sectors are construction, automotive and machineries. The recent years have brought an increasing trend of steel consumption in the ASEAN countries due to the positive economic growth. So these countries are now expanding their steel producing capacities in order to achieve self-reliance in this sector. The construction of the first ever Blast Furnace-based steel plant in Malaysia is a landmark project for attaining sufficiency in meeting national steel demand. Generally, an iron and steel making plant has all the developed facilities starting from the handling of raw materials to the final finished products. Once in operation, these plants require periodic major overhauls and up-grading besides routine repairs and maintenance activities to ensure their smooth operations. This study discusses an integrated approach named ‘Production+’ which was envisioned for the revamping and expansion of a public sector iron and steel making plant in Pakistan. The plant was commissioned in 1984 – 85 and after 20 years of its successful operation in 2004, the then management decided to revamp and expand its production capacity of steel up to 3.0 million metric ton (mmt) per year. For achieving this objective, it was planned that numerous strategic decisions would be taken during the course of the revamping and expansion program. This mainly included the improvement of existing maintenance practices to a more advanced plant maintenance level, energy conservation program that cut down energy and utility costs, and process optimization to detect and remove bottlenecks and inefficiencies in the production process. So, in order to get the maximum synergy it was proposed to integrate all the revamping and expansion program activities under one program named Production+. The + (plus) stands for more production, profitability, quality and serviceability of the steel making facility on a sustainable basis